Analysing the Effect of NPK on Cabbage Production in Kabale Municipality. - Mugyenyi, Joab (Kabale University, 2024)
The research project was carried out to determine the quality and yield responses of cabbages to different rates of fertilizers in the demonstration garden of the Faculty of Agriculture and Environmental Sciences of Kabale University. The study's specific objectives were to; evaluate the effects of NPK on cabbage production in Kabale Municipality, assess the influence of NPK on cabbage quality attributes, and provide recommendations for optimal inorganic fertilizer utilization for sustainable cabbage production in Kabale Municipality.